Indoor Air Quality Assessment in a Radiantly Cooled Tropical Building: a Case Study - Qi Jie KWONG; Nor Mariah ADAM; Tezara CIONITA; Vijay R RAGHAVAN; Mohd Fareq ABD MALEK (Tehran University of Medical Sciences, 2015)
Background: Many studies have been conducted to assess the indoor air quality (IAQ) of buildings throughout the world because it is closely related to comfort, safety and work productivity of occupants. However, there is still lack of available literature about IAQ in tropical buildings that apply radiant cooling systems in conditioning the indoor air. Methods: This paper reports the results obtained from an IAQ audit that was conducted in a new radiantly cooled building in Malaysia, by focusing on the IAQ and thermal comfort parameters. Results: It was identified that the measured concentration levels for the five indoor air contaminants (CO, CO2, TVOC, formaldehyde and respirable particulates) were within the threshold limit values (TLVs) specified in the IAQ guidelines. Besides, no significant difference was found between the contaminant levels in each floor of the studied building, and a majority of the respondents did not encounter any form of physical discomfort. There is a risk of condensation problem, judging from the measured RH level. Conclusion: An increase of airflow rate and more dehumidification work in the studied building can be made to improve IAQ and prevention of condensation problem. Nevertheless, these schemes should be implemented carefully to avoid occupants' discomfort. Relocation of workstations was suggested, especially for the lower floors, which had higher occupancy levels.   Keywords: Indoor air quality (IAQ), Radiant cooling systems, IAQ audit, Indoor air contaminants, Condensation